Gross Anatomy of Scapula of Mudhol Hound Dog - Mutturaj, R.P. (Indian Journal of Veterinary Anatomy, 2020)
The gross morphological features of scapulae of mudhol hound dogs were studied. The scapula was flat and triangular in shape. The height of the spine was greatest at the glenoid angle with an average of 40mm andwidth of the spine was greater towards the dorsal border with an average of 13.4mm. The average distance between cranial and caudal angle was 8cm. The distance between cranial and caudal borders at the middle of thescapula was 9.16 cm and the same at the glenoid angle was about 4.06cm. The average length of scapula at cranial border was 17.75 cm, at the caudal border was 15.1cm and at the middle was about 17cm.The thickening and rolling of scapular spine caudally indicated attachments of heavy muscles characteristics of hunting behaviour of mudhol hound dogs.